Inverse Problems Recent Advances and Applications - Kyrchei, Ivan I. (IntechOpen, 2023)
Inverse Problems - Recent Advances and Applications examines some recent advances in inverse problems, new aspects of their mathematical modeling of inverse problems regarding in relation to their applications in physical systems and used the computational methods used. It consists of five chapters divided into two sections. Section 1, "Modeling and Formulations of Inverse Problems", discusses new approaches to modeling and formulations of inverse problems in some physical systems. Section 2, "Some Computational Aspects", contains research related to mathematical methods of solving some inverse problems.